Completing square

Solve the quadratic equation:

m2=4m+20 using completing the square method

Result

m1 =  6.899
m2 =  -2.899

Solution:

Solution in text m1 =
Solution in text m2 =

Checkout calculation with our calculator of quadratic equations.








Leave us a comment of example and its solution (i.e. if it is still somewhat unclear...):

Showing 0 comments:
1st comment
Be the first to comment!
avatar




Looking for help with calculating roots of a quadratic equation?

Next similar examples:

  1. Non linear eqs
    q2_non_linear Solve the system of non-linear equations: 3x2-3x-y=-2 -6x2-x-y=-7
  2. Solve equation
    hrusky_2 solve equation: ?
  3. Quadratic equation
    parabola_1 Solve quadratic equation: 2x2-58x+396=0
  4. Product
    floring The product of two consecutive odd numbers is 8463. What are this numbers?
  5. Square root 2
    parabola_2 If the square root of 3m2 +22 and -x = 0, and x=7, what is m?
  6. Quadratic equation
    Parabola_tangent Quadratic equation ? has roots x1 = 80 and x2 = 78. Calculate the coefficients b and c.
  7. Calculation
    pocty How much is sum of square root of six and the square root of 225?
  8. Solve 3
    eq2_4 Solve quadratic equation: (6n+1) (4n-1) = 3n2
  9. Equation
    calculator_2 Equation ? has one root x1 = 8. Determine the coefficient b and the second root x2.
  10. Discriminant
    Quadratic_equation_discriminant Determine the discriminant of the equation: ?
  11. Roots
    parabola Determine the quadratic equation absolute coefficient q, that the equation has a real double root and the root x calculate: ?
  12. Quadratic equation
    kvadrat_2 Find the roots of the quadratic equation: 3x2-4x + (-4) = 0.
  13. Expression with powers
    eq222_9 If x-1/x=5, find the value of x4+1/x4
  14. Evaluation of expressions
    eq222_10 If a2-3a+1=0, find (i)a2+1/a2 (ii) a3+1/a3
  15. Algebra
    parabol_3 X+y=5, find xy (find the product of x and y if x+y = 5)
  16. Expressions 3
    parabola2_1 If k(x+6)= 4x2 + 20, what is k(10)=?
  17. Theorem prove
    thales_1 We want to prove the sentense: If the natural number n is divisible by six, then n is divisible by three. From what assumption we started?